2014
DOI: 10.1111/nph.12772
|View full text |Cite
|
Sign up to set email alerts
|

Increased water‐use efficiency does not lead to enhanced tree growth under xeric and mesic conditions

Abstract: SummaryHigher atmospheric CO 2 concentrations (c a ) can under certain conditions increase tree growth by enhancing photosynthesis, resulting in an increase of intrinsic water-use efficiency ( i WUE) in trees. However, the magnitude of these effects and their interactions with changing climatic conditions are still poorly understood under xeric and mesic conditions.We combined radial growth analysis with intra-and interannual d 13 C and d 18 O measurements to investigate growth and physiological responses of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
137
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 66 publications
20
137
1
Order By: Relevance
“…Our dual-isotope analysis, however, suggests that both species reacted by small and non-significant reductions of stomatal conductance (g s ) and net carbon assimilation [51] (Figure 7). Higher iWUE in P. sylvestris reflected its tighter stomatal control than P. nigra and thus a more isohydric strategy oriented to reduce water spending in accordance with previous results from xeric sites [2,75]. Earlier stomata closing in P. sylvestris might contribute to maintaining hydraulic pressure below dangerous levels at this site, but its conservative strategy might reduce its ability to compete for light if P. nigra grows taller faster.…”
Section: Intrinsic Water-use Efficiencysupporting
confidence: 88%
“…Our dual-isotope analysis, however, suggests that both species reacted by small and non-significant reductions of stomatal conductance (g s ) and net carbon assimilation [51] (Figure 7). Higher iWUE in P. sylvestris reflected its tighter stomatal control than P. nigra and thus a more isohydric strategy oriented to reduce water spending in accordance with previous results from xeric sites [2,75]. Earlier stomata closing in P. sylvestris might contribute to maintaining hydraulic pressure below dangerous levels at this site, but its conservative strategy might reduce its ability to compete for light if P. nigra grows taller faster.…”
Section: Intrinsic Water-use Efficiencysupporting
confidence: 88%
“…The d 13 C in tree-ring cellulose (d 13 C tree-ring ) can be used to document changes in the intrinsic water use efficiency, defined as the ratio of leaf CO 2 assimilation (A) to stomatal conductance (g s ) (L evesque et al, 2014;Saurer et al, 2014;Frank et al, 2015). Some studies found that d 13 C tree-ring was unaffected by thinning, implying either that g s and A did not change or that they changed with the same magnitude, that is, the ratio A/g s remained constant (Martin-Benito et al, 2010;Powers et al, 2010;Brooks & Mitchell, 2011;Moreno-Gutierrez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Leonardi et al (2012) conclude that the temporal variation in δ 13 C in their long-term isotope tree-ring chronologies for 53 sites worldwide supports the hypothesis of an active plant mechanism that maintains a constant ratio between intercellular and ambient CO 2 concentrations. Lévesque et al (2014) reported, from their δ 13 C tree-ring data, an increase in iWUE over the last 50 years in the range of 8 to 29 % for xeric and mesic sites in the Alps and Switzerland. At their sites, drought-induced stomatal closure has reduced transpiration at the cost of reduced carbon uptake and growth.…”
Section: Consistency With Previous Studiesmentioning
confidence: 99%
“…There is a rich body of literature on changes in 13 C isotopic discrimination and iWUE and on observational evidence from δ 13 C tree-ring records McCarroll and Loader, 2004;Fichtler et al, 2010;Leonardi et al, 2012;Churakova , Sidorova, S;Lévesque et al, 2014;Liu et al, 2014b;Saurer et al, 2014;Hartl-Meier et al, 2015;Voelker et al, 2016), free-air CO 2 enrichment (FACE)-type experiments (Battipaglia et al, 2013;Klein et al, 2016), δ 13 C site measurements (Pataki et al, 2003;Bowling et al, 2014), and δ 13 C paleodata (Voelker et al, 2016). These data generally suggest small to moderate decadal-to-century-scale changes in discrimination that correspond to a 20th century increase in iWUE On the order of 20 % and physiological control towards a constant ratio of the partial pressure of CO 2 within the leaf's substomatal cavities to the CO 2 pressure outside the leaf (c i /c a ; Saurer et al, 2004;Leonardi et al, 2012;Frank et al, 2015) and, more generally, a pattern of stomatal optimization towards minimizing water loss per unit carbon assimilated (Voelker et al, 2016).…”
mentioning
confidence: 99%